DAYA TARIK MOROTAI SEBAGAI DESTINASI WISATA SEJARAH DAN BAHARI - Marhanani Tri Astuti; Any Ariani Noor (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2016)
Morotai is historical and marine tourism destination as well as one of the National Tourism Strategic Destinations (NTSD). The carrying capacity in Morotai is different than other destinations that makes it a priority destination and expected to contribute on bringing in 20 million international tourists in 2019. The study then tried to analyze the tourism potential and tourist attraction in Morotai to make it as a prepared destination to welcome the international visitor. The aim of this study is to analyze the readiness of Morotai as historical and marine tourist attraction so that it could fulfill the service standards of all the 4A tourism components. The analysis used the 4A tourism components (attraction, accessibility, ancillary, and amenity) as the method. Observation, interviews and documentation conducted at Morotai to collect data about tourism potential and supported with focus group discussion (FGD). SWOT Analysis conducted to identify the tourism components and followed by defining the best tourism strategic for Morotai. The result shown that Morotai could attract visitors through the history of World War II and marine tourism. To develop it, Morotai should fulfil the minimum criteria of tourism component that international visitors needed.